MENINGKATKAN KEMAHIRAN SISWA KELAS VIII A PADA PEMBELAJARAN LOMPAT TINGGI DENGAN MENGGUNAKAN METODE BERMAIN DI LINGKUNGAN PANTAI DI SMP NEGERI 1 PAGA - Hendrikus Dote (Yayasan Akrab Pekanbaru, 2019)
The purpose of applying the play model in the coastal environment is students who are involved in learning activities and encourage students to be more creative, fostering confidence in learning. The method used in this study is Classroom Action Research (CAR). This research was conducted at SMP Negeri 1 Paga, Paga Subdistrict, Sikka Regency, with the research subjects being VIIIA class students who studied 21 students. The researcher acts as an observer. Data collection is done by observation, tests and questionnaires. To analyze qualitative data used observation sheet of student activities and questionnaires used to determine student responses, while for quantitative data using tests, in order to find out student learning outcomes. Classroom Action Research (CAR) consists of 2 cycles with the same subject matter, where each cycle consists of four stages, namely: planning, action, observation and reflection. Student learning outcomes showed a fairly good increase seen from the average student learning outcomes each cycle. The average student learning outcomes in cycle I is 7.80 and cycle II is 8. This is supported again by the observation of students which increases student activity significantly and student responses to the application of the method of playing in the coastal environment with discussion of cycle 1 64.86% and cycle 2 92.43%.